Leproid granuloma syndrome in a dog in the city of Pelotas: Case report - Camelo Júnior, Francisco; Castagnara Alves, Caroline; Gabriela Mello Fonseca, Maria; de Azevedo Soares, Matheus; Andrade de Bilhalva, Maurício; Salardi Alves de Brito, Risciela (Pubvet, 2019)
The leproide canine granuloma syndrome is an uncommon disease of mycobacterial etiology, probably underdiagnosed. Clinically, cutaneous lesions occur preferentially in regions more susceptible to insect bites, such as ears and head. In most of the reported cases, the affected dogs present good general health and are found as a clinical finding, without involvement of other organs. The diagnosis can be quite suggestive by the racial pattern. However, confirmation of the diagnosis should be made through biopsy or histopathology. In most cases the CAAF is the exam of choice, for practicality, speed and safety. Most cases are self-limiting and regress spontaneously between one and three months after the initial onset, but usually occur with localized or generalized chronic skin infection. Thus, the objective of the present study is to report the case of a dog with definitive diagnosis of canine leprosy granuloma syndrome in Pelotas city, clarifying the behaviors made with the patient from the care to the return of the localized lesion.
Keywords: cytological; clinical; histopathological; leprosy; treatment